Short communication: age2exhume – a MATLAB/Python script to calculate steady-state vertical exhumation rates from thermochronometric ages and application to the Himalaya - van der Beek, Peter; Schildgen, Taylor F. (Geochronology (Göttingen. Online), 2023)
Interpreting cooling ages from multiple thermochronometric systems and/or from steep elevation transects with the help of a thermal model can provide unique insights into the spatial and temporal patterns of rock exhumation. Although several well-established thermal models allow for a detailed exploration of how cooling or exhumation rates evolved in a limited area or along a transect, integrating large, regional datasets in such models remains challenging. Here, we present age2exhume, a thermal model in the form of a MATLAB or Python script, which can be used to rapidly obtain a synoptic overview of exhumation rates from large, regional thermochronometric datasets. The model incorporates surface temperature based on a defined lapse rate and a local relief correction that is dependent on the thermochronometric system of interest. Other inputs include sample cooling age, uncertainty, and an initial (unperturbed) geothermal gradient. The model is simplified in that it assumes steady, vertical rock uplift and unchanging topography when calculating exhumation rates. For this reason, it does not replace more powerful and versatile thermal–kinematic models, but it has the advantage of simple implementation and rapidly calculated results. We also provide plots of predicted exhumation rates as a function of thermochronometric age and the local relief correction, which can be used to simply look up a first-order estimate of exhumation rate. In our example dataset, we show exhumation rates calculated from 1785 cooling ages from the Himalaya associated with five different thermochronometric systems. Despite the synoptic nature of the results, they reflect known segmentation patterns and changing exhumation rates in areas that have undergone structural reorganization. Moreover, the rapid calculations enable an exploration of the sensitivity of the results to various input parameters and an illustration of the importance of explicit modeling of thermal fields when calculating exhumation rates from thermochronometric data.